A Paraíba no contexto nacional, regional e interno - Constantino Cronemberger Mendes; Ignácio Tavares de Araújo Júnior; Anna Paola Fernandes; Diego Mendes Lyra; Geraldo Lopes de Oliveira; Carlos Gonçalo de Oliveira; Neuma Benigno da Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– The economy of Paraíba has changed is productive and social structure. This paper aims to describe this process highlighting the recent economic changes and its relationship with regional and national economy. The demographic and productive structures demonstrate the possible internal heterogeneities, in terms of population, sector and production. The data show a rate of growth of Gross Domestic Product (GDP) higher than the average annual regional and national levels, but with a Human Development Index (HDI) is still considerably less than the same spheres. In education, the State has show remarkable progress, particularly in elementary school, whose attendance approaching 100%. However, the level of schooling the state's population is still below the national and ergional averages. The sector dynamics are services and industry, with the share of employment arising and, on the other hand, showing the fall of the share in agriculture sector. The examination of intersate and foreign trade flows reveals is deficit, concentrated in a few products exported and higher value added and diversification in its imports. From the internal point of view, population, production activity and employment are highly concentrated in two (or three) regions, particularly Jo\~ao Pessoa (capital) and Campina Grande. Through the use of location quotients, it was possible to identify of specialization in industry and services sector and some internal regions. The gap analysis provides additional insight on the structural components of the growht of the Paraíba's regions. Finally, data on the labor market of Paraíba municipalities reveal differences both in qualifying and salaries.
Keywords: R1; R10; R11; R12; 330; Paraíba; regional-sectoral analysis; differential-structural indicators